Social capital, a theory for operations management: a systematic review of the evidence - Matthews, Rupert L.; Marzec, Peter E. (International journal of production research, 2012)
As Pfeffer ( 1993 ) states that until agreement is reached on a subject, progress may be slow. This paper converges the discussions on social capital in the operations management literature by way of a systematic literature review of 3- and 4-star journals. Human resource management, voluntary work and entrepreneurship were identified as minor themes within the review and thus potentially underexplored areas. Quality management, project management and new product development show significant use of social capital and particularly the role of social capital in the intrafirm environment. Finally, supply chain management shows the most significant use of social capital, particularly in explaining the characteristics of buyer-supplier relationships and how these impact inter-firm performance. Areas of future research are presented that draw on all forms of social capital to explore how they may be affect by contextual factors. The paper concludes by proposing a conceptual model of social capital for use within operations management.